Engendering the Republic of Letters: Reconnecting Public and Private Spheres in Eighteenth-Century Europe - Dalton, Susan (McGill-Queen's University Press, 2004)
Being women provided them with a particular perspective, expressed first-hand through their letters. Dalton shows how Lespinasse, Roland, Renier Michiel, and Mosconi grappled with differences of ideology, social status, and community, often through networks that mixed personal and professional relations, thus calling into question the actual separation between public and private spheres. Building on the work of Dena Goodman and Daniel Gordon, Dalton shows how a variety of conflicts were expressed in everyday life and sheds new light on Venice as an important eighteenth-century cultural centre.
Google-Books-ID: v_xVAdkfCokC
Keywords: Literary Collections / Letters; Social Science / Women's Studies